FRI0182 Erosions at the sacroiliac joints and fatty lesions at the spine are the most discriminant lesions for recent onset axspa recognition. (12th June 2018) - Moltó, A.; Gossec, L.; Lefevre-Colau, M.; Beaufort, R.; Foltz, V.; Laredo, J.; Richette, P.; Dieudé, P.; Goupille, P.; Feydy, A.; Dougados, M.
Abstract : Objectives: To evaluate the performances of MRI (SIJ and Spine) structural lesions suggestive of axSpA for its recognition. Methods: Observational cross-sectional national multicentre study. Patients : a) Recent onset axSpA patients: first, a sample of 100 patients representative in terms of imaging abnormalities of the global DESIR recent onset axSpA cohort based on the results of the previously published central reading of baseline films of DESIR were selected. b) Recent onset CBP patients: consecutive in- and outpatients consulting for recent mechanical CBP, initiating before the age of 45 y and with a maximum age of 50 y, in four tertiary care Hospitals were included in the study. Imaging: MRI scans (T2-STIR and T1 sequences) of the SIJ and cervico-thoracic and thoraco-lumbar spine were performed in both groups with identical protocol. Central reading: an experienced reader (AM) centrally read all MRI scans, blinded for clinical diagnosis. Statistical analysis: prevalence of lesions suggestive of axSpA was compared in both groups. Sensitivity, specificity and positive likelihood ratio (LR+) of each lesion were calculated. Results: A total of 98 patients with recent onset CBP were included, and compared to 100 recent onset axSpA patients. Age and gender were comparable (mean (SD) 36.2 (9.9) vs. 32.2 (8.7)y, and 41.8% and 45% males, in the CBP vs. axSpA groups, respectively). Prevalence of chronic lesions of the SIJ was significantly greater in the axSpA group. Presence of at least 3 subchondral bone erosions at the SIJ performed the best for axSpA discrimination. Prevalence of chronic lesions of the spine was comparable in the two groups. The presence of at least 5 fatty lesions was the most discriminant, with high specificity. Conclusions: Presence of at least 3 erosions at the MRI-SIJ and at least 5 fatty lesions at the MRI-spine seemed to performed well for axSpA recognition. Disclosure of Interest: None declared